Improving Writing Ability In Descriptive Text By Using Picture Media At The First Year Students Of Sman 1 Pace Nganjuk - Imam Muadib (STKIP PGRI Nganjuk, 2021)
Based on the researcher’s, to improving writing ability at the first years students of SMAN I Pace Nganjuk is very difficult. There are many problems which are often faced by the students. There is student’s difficulty to applying their ideas and so on. And now researcher wants to trying improving student’s writing ability using picture media. The objective of the study was to describe improving student’s writing ability in descriptive text using picture media at the first year’s students of SMAN I Pace Nganjuk. This research uses CAR (classroom Action Research). The steps of CAR needs repeatedly process until get the good result better than before. In this research, the researcher used CAR as implement a strategy in writing class activity. The data of the study were gathered through pre-test, cycle 1, cycle 2, and cycle 3. The population of the first year students was 324. In order to make easier, the researcher took a sample as the subject of this study. The researcher used purposive sampling to take the subjects of this study. They were 36 first year students of SMAN I Pace Nganjuk of the 2012/2013 academic year. From the data and analysis of the students’ writing achievement, the study had found that the minimal score of pre-test is 40 and maximal score was 75, of the cycle 1 minimal score is 55 and maximal score was 75, of the cycle 2 minimal score is 60 and maximal score was 80 where as the minimal score of the cycle 3 was 65 and maximal score was 85. Based on the analysis of data which was taken at 36 students of the first years students in SMAN I Pace Nganjuk. The successfully improvement from the improvement of writing descriptive text using picture media could be seen of the students writing score from pre-test until cycle 3. Before applied picture media in teaching writing, the students writing achievement was not satisfactory. And after the cycle was done, and the student’s score of pre-test and cycle 1 – 3 counted by using SPSS 11, the conclusion of this research showed that picture media could improve student’s writing ability there, because on the research researcher found improving student’s writing score. From the improvement writing score, researcher could give suggestion for teacher there are she should evaluate the condition of the class, prepare the interesting picture for writing and pay attention to every student, especially to the low students. And the suggestion for students they are the students should build their motivation and intention, they should be active in learning process.